PERAN GLUKOSAMIN PADA OSTEOARTRITIS - Utami, Pratiwi; Kalangi, Sonny J.R.; Pasiak, Taufiq (UNIVERSITAS SAM RATULANGI, 2012)
Abstract: Osteoarthritis is a degenerative disease and manifests itself as the most common type of arthritis affecting older people. This disease can cause significant pain and functional disability in the affected individuals. The therapy for osteoarthritis is easily available but the results are without certainty. Symptomatically therapeutic agents such as acetaminophen and NSAIDs are only beneficial for relieving the symptoms. Unfortunately, these agents can trigger severe side effects in some patients or may be contraindicated. Glucosamine has been evaluated in several studies as an agent to relieve pain, increase functional activity, and slow the progression of osteoarthritis, especially in the knees. Studies have reported some improvement in pain and disability in osteoarthritic patients related to the use of glucosamine. Based on the current evidence, a combination of glucosamine sulfate and chondroitin sulfate shows the greatest potential as a therapeutic intervention for patients who might risk side effects from other oral medications currently in vogue. However, research is still needed to explore the benefits of glucosamine or its combination forms in order to ensure safety for long-term use. Keywords: osteoarthritis, glucosamine, pain. Â Â Abstrak: Osteoartritis merupakan penyakit degeneratif yang menyebabkan rasa nyeri dan cacat fungsional pada individu yang terkena dan umumnya mempengaruhi lanjut usia. Kemajuan dalam pengobatan osteoartritis relatif tersedia tetapi belum secara pasti untuk mengobatinya. Terapi andalan seperti asetaminofen dan obat NSAID hanya untuk mengobati gejala, tetapi dapat memicu efek samping yang parah pada pasien atau mungkin merupakan kontraindikasi. Beberapa studi mengemukakan glukosamin sebagai agen untuk menghilangkan rasa nyeri, meningkatkan aktivitas fungsional, dan memperlambat progresivitas osteoarthritis, terutama pada lutut. Juga telah dilaporkan perbaikan dalam rasa nyeri dan kecacatan yang terkait dengan penggunaan glukosamin baik sebagai agen tunggal maupun bentuk kombinasi glukosamin sulfat dengan kondroitin sulfat. Penggunaan produk kombinasi tersebut tampaknya memiliki potensi besar untuk pasien yang berisiko akibat efek samping terapi oral. Masih dibutuhkan penelitian lanjut mengenai manfaat dan kemanan glukosamin terutama pada pemakaian jangka panjang. Kata kunci: osteoartritis, glukosamin, nyeri.